Stigma and its influencing factors in female patients with high-risk HPV infection: a cross-sectional study - Gong, Lili; Li, Xiaonan; Hou, Dan (Frontiers in Psychiatry, 2025)
BackgroundStigma associated with high-risk human papillomavirus (HR-HPV) infection presents a significant barrier to both the uptake of cancer screening and the completion of follow-up care after a positive screening result. Identifying the factors that contribute to this stigma is essential for healthcare professionals to design targeted interventions aimed at reducing stigma and improving patient engagement across the continuum of care.ObjectivesThis exploratory study aimed of this study is to explore the current situation of stigma in HR-HPV patients and its influencing factors.MethodA cross-sectional study was performed from May to October 2023. Two hundred female patients with HR-HPV infection were recruited from the Department of Gynecology at the General Hospital of Northern. Demographic parameters, disease-related variables, psychosocial factors, psychological resilience, and rumination data were obtained by self-reported questionnaires.ResultsOf the 200 patients, 37 (18.5%) indicated a low degree of stigma, 152 (76.0%) indicated a moderate level, and 11 (5.5%) indicated a high level. Stigma scores exhibited a positive correlation with rumination scores and a negative correlation with psychological resilience scores. Monthly personal income, recurring infections, psychological resilience, and rumination were recognized as independent variables affecting stigma. This exploratory study revealed that psychological resilience and rumination collectively explained 23.4% of the variance in stigma.ConclusionPersonal monthly income, recurring infections, psychological resilience, and rumination were influential factors contributing to stigma in HR-HPV patients. Subsequent research should prioritize the development and integration of interventions aimed at eliminating stigma.